2016
DOI: 10.1016/j.ijrobp.2016.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Multicenter Clinical Trial of Bone Marrow–Sparing Intensity Modulated Radiation Therapy With Concurrent Cisplatin for Stage IB-IVA Cervical Cancer

Abstract: SummaryWe performed an international phase II trial to test the Purpose: To test the hypothesis that intensity modulated radiation therapy (IMRT) reduces acute hematologic and gastrointestinal (GI) toxicity for patients with locoregionally advanced cervical cancer. hypothesis that intensity modulated radiation therapy (IMRT) would reduce the acute toxicity for locoregionally advanced cervical cancer. For the 83 patients enrolled, acute gastrointestinal toxicity was significantly reduced with both IMRT and posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 28 publications
(52 reference statements)
0
11
1
Order By: Relevance
“…The V10-20Gy has been optimised in prospective research, which have demonstrated reductions in HT. 14,16 We found that the V10Gy < 90%, V20Gy < 75% and V30Gy < 60% could be met in 100% of cases where VMAT margins were utilised (Table S1), suggesting that these objectives could be prioritised. The V40Gy < 37% was achieved in 83.3% of cases in our cohort; therefore, aiming to achieve this with a relatively low priority is feasible, until further prospective studies are available.…”
Section: Haematological Toxicitymentioning
confidence: 94%
See 4 more Smart Citations
“…The V10-20Gy has been optimised in prospective research, which have demonstrated reductions in HT. 14,16 We found that the V10Gy < 90%, V20Gy < 75% and V30Gy < 60% could be met in 100% of cases where VMAT margins were utilised (Table S1), suggesting that these objectives could be prioritised. The V40Gy < 37% was achieved in 83.3% of cases in our cohort; therefore, aiming to achieve this with a relatively low priority is feasible, until further prospective studies are available.…”
Section: Haematological Toxicitymentioning
confidence: 94%
“…7,11 12 These studies are limited by their bone marrow delineation methods using CT only, and therefore, whether these objectives are applicable to functionally defined ABM cannot be determined. 14,16 More recent studies have focussed on correlations between HT and functionally defined bone marrow; however, results are also inconsistent. In these studies, there is a heterogeneity in image modality used for ABM delineation.…”
Section: Haematological Toxicitymentioning
confidence: 99%
See 3 more Smart Citations